ANALISIS KEBERHASILAN PENDIDIKAN ANAK USIA DINI BUNDA KREATIF KOTA DUMAI - Sahir Sahir; Sumardi Sumardi; Wilson Wilson (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2018)
This research was conducted at the early childhood education Bunda KreatifDumai City in 2015 by using qualitative research methods. The research data was obtainedthrough interviews, observation and documentation study. The informants in this study DumaiCity Department of Education/Supervisors, Principals, teachers, pupils and the Mayor of theSchool Committee. This study was conducted to analyze in depth about the success of earlychildhood Bunda Kreatif Dumai City in implementing the learning process as the educator ofintelligence generation at an early age where various achievements obtained include: ChampionCluster best level of Riau Province in 2015, the first winner of environmentally sound best levelDumai City as 4 times in a row, Guru achievement represents Dumai in Riau Province to thelevel of 2015, the principal as well as the chairman of the steering committee for the ClusterWorking Group Principal (CWGP) Dumai city and the only park early childhood education whohave education consultant.